Repeatability of ventricular arrhythmia characteristics on the exercise-stress test in RYR2-mediated catecholaminergic polymorphic ventricular tachycardia. Issue 2 (12th November 2022) - Peltenburg, Puck J; Pultoo, Sanjeev N J; Tobert, Kathryn E; Bos, J Martijn; Lieve, Krystien V V; Tanck, Michael; Clur, Sally-Ann B; Blom, Nico A; Ackerman, Michael J; Wilde, Arthur A M; van der Werf, Christian
Abstract: Aims: In catecholaminergic polymorphic ventricular tachycardia (CPVT), the exercise-stress test (EST) is the cornerstone for the diagnosis, risk stratification, and assessment of therapeutic efficacy, but its repeatability is unknown. We aimed to test the repeatability of ventricular arrhythmia characteristics on the EST in patients with CPVT. Methods and results: EST-pairs (ESTs performed within 18 months between 2005 and 2021, on the same protocol, and without or on the exact same treatment) of patients with RYR2-mediated CPVT from two specialized centres were included. The primary endpoint was the repeatability of the maximum ventricular arrhythmia score [VAS: 0 for the absence of premature ventricular contractions (PVCs); 1 for isolated PVCs; 2 for bigeminal PVCs; 3 for couplets; and 4 for non-sustained ventricular tachycardia]. Secondary outcomes were the repeatability of the heart rate at the first PVC and the ΔVAS (the absolute difference in VAS between the EST-pairs). A total of 104 patients with 349 EST-pairs were included. The median duration between ESTs was 343 (interquartile range, 189–378) days. Sixty (17.2%) EST-pairs were off therapy. The repeatability of the VAS was moderate {Krippendorf α, 0.56 [95% confidence interval (CI), 0.48–0.64]}, and the repeatability of the heart rate at the first PVC was substantial [intra-class correlation coefficient, 0.78 (95% CI, 0.71–0.84)]. The use of medication was associated with a higher odds for a ΔVAS > 1 (odds ratio = 3.52; 95% CI, 2.46–4.57; P = 0.020). Conclusion: The repeatability of ventricular arrhythmia characteristics was moderate to substantial. This underlines the need for multiple ESTs in CPVT patients and CPVT suspicious patients and it provides the framework for assessing the therapeutic efficacy of novel CPVT therapies. Graphical Abstract: Graphical Abstract